Performance of the ResistancePlus MG diagnostic test for Mycoplasma genitalium using samples collected with Hologic Aptima Specimen Collection kits. Issue 2 (20th January 2020) - Murray, Gerald L.; Danielewski, Jennifer; Bradshaw, Catriona S.; Williamson, Deborah A.; Birnie, Joshua; Su, Jenny P.; De Petra, Vesna; Tan, Lit Y.; Wee, Rachel; Machalek, Dorothy A.; Read, Tim R. H.; Garland, Suzanne M.
Abstract : Introduction. ﻿ ﻿﻿﻿ Mycoplasma genitalium is a sexually transmitted organism with high levels of resistance to the recommended first-line therapy, azithromycin. The ResistancePlus MG test concurrently detects M. genitalium, and the presence of macrolide-resistance mutations (MRM). European, UK and Australian guidelines recommend a diagnostic test that reports MRM to optimize treatment through resistance-guided therapy. Hence, for samples collected for use on other platforms, reflex testing using the ResistancePlus MG test would be beneficial. Aim. To validate the ResistancePlus MG assay using samples collected in Aptima buffer for testing on the Hologic Panther. Methodology. Positive ( n =99) and negative ( n =229) clinical samples collected in Aptima buffer were extracted on the MagNA Pure 96 (Roche Diagnostics), and tested with the ResistancePlus MG test on the LightCycler 480 II (Roche Diagnostics). Results were compared to matched samples collected using standard sample collection (urine or swab resuspended in PBS), with positive percent agreement (PPA), negative percent agreement (NPA) and Cohen's Kappa statistic. Results. The ResistancePlus MG test had high performance with a 200 µl input volume (PPA/NPA for M. genitalium detection, 92.9 % [95 % confidence interval (CI): 85.5–96.9]/100 % [95 % CI: 97.9–100], MRM detection, 96.9 % [95 % CI: 88.2–99.5]/85.7 % [95 % CI: 66.4–95.3]) and for 1 ml input volume (PPA/NPA for M. genitalium detection, 95.9%/96.6%, MRM detection, 98.4%/90.3%). Samples remained positive after storage at room temperature beyond the manufacturer-recommended storage of <60 days (mean storage time for 1 ml extraction: 129 days). Conclusion. Samples collected using Aptima collection kits are suitable for reflex testing using the ResistancePlus MG test, allowing detection of macrolide resistance.